Towards enhanced sodium storage of anatase TiO2via a dual-modification approach of Mo doping combined with AlF3 coating. Issue 29 (22nd July 2020) - Bai, Xue; Li, Tao; Gulzar, Umair; Venezia, Eleonora; Chen, Lin; Monaco, Simone; Dang, Zhiya; Prato, Mirko; Marras, Sergio; Salimi, Pejman; Fugattini, Silvio; Capiglia, Claudio; et al.
Abstract : In order to push forward the concept of sodium-ion batteries, a facile and cost effective synthesis method for achieving high performance anodes has been developed based on a dual modification of pristine anatase TiO2 . Abstract : Recent studies on anatase TiO2 have demonstrated its capability of performing as an anode material for sodium-ion batteries (SIBs) even though, due to poor conductivity, realistic applications have not yet been foreseen. In order to try to address this issue, herein, we shall introduce a cost effective and facile route based on the co-precipitation method for the synthesis of Mo-doped anatase TiO2 nanoparticles with AlF3 surface coating. The electrochemical measurements demonstrate that the Mo-doped anatase TiO2 nanoparticles deliver an ∼40% enhanced reversible capacity compared to pristine TiO2 (139.8 vs. 100.7 mA h g −1 at 0.1 C after 50 cycles) due to an improved electronic/ionic conductivity. Furthermore, upon AlF3 coating, the overall system can deliver a much higher reversible capacity of 178.9 mA h g −1 (∼80% increase with respect to pristine TiO2 ) with good cycling stability and excellent rate capabilities of up to 10 C. The experimental results indicate that the AlF3 surface coating could indeed effectively reduce the solid electrolyte interfacial resistance, enhance the electrochemical reactivity at the surface/interface region, and lower the polarization during cycling. The improved performance achieved using a cost-effective fabrication approach makes the dually modified anatase TiO2 a promising anode material for high-performance SIBs.